Recommendations for Degreening Florida Fresh Citrus Fruits - Mark A. Ritenour; William M. Miller; Wilfred W. Wardowski (EDIS)
Early varieties of citrus fruit in Florida usually meet legal maturity standards before the peel attains the characteristic varietal color and therefore require degreening. Occasionally, later maturing varieties may similarly require degreening. The degreening process, which involves the use of ethylene gas in specially constructed degreening rooms, destroys the chlorophyll and allows the yellow or orange peel to predominate. This document is Cir 1170, Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2003.